Response of Management Practices on Rooting Pattern of Albizia procera and Their Effect on Grain Yield of Soybean and Wheat in Agrisilviculture System - Newaj, Ram; Yadav, R.S.; Dar, Shabir Ahmad; Singh, Ajit; Shanker, Arun K. (Indian Journal of Agroforestry, 2020)
Above and belowground competition for growth resources between tree and crop can be minimized by pruning, putting soil barrier between tree and crop and avoiding moisture stress through providing required irrigation to the crop. The role of these management practices on production of understorey crop in grisilviculture might be less during initial years but their effect may be increased with increasing age of trees. The above and belowground management of tree component in agrisilviculture system are poorly understood. The height, dbh and crown diameter of trees were less in soil barrier and pruning as compared to without barrier and tree allowed to grow normally. On other hand, irrigation given to the crop as per their requirement had better growth than one or two irrigation. The grain yield of intercrop (soybean) in aqrisilviculture system was almost similar to that of pure crop during 1st year of tree plantation, but grain yield of intercrop increased by 10.57 and 33.64% respectively during second and third years with 70% pruning over trees allowed to grow normally. After four years, the yield was 132.50% higher in 70% pruning than trees allowed to grow normally. The grain yield of crop under soil barrier was 13.89 to 20.06% higher over without barrier during different years. Similar results were also obtained in case of wheat but the benefits of irrigation was more on grain yield during first two years and after that pruning took a lead over irrigation during third and fourth year. The yield benefit in wheat crop due to pruning in fifth year was 41'5% over tree allowed to grow normally. The greater horizontal root spread was observed in pure tree than agrisilviculture system. The lateral spread of root was comparatively less in those trees in which pruning was done up to 70% tree height than trees allowed to grow normally. Most of the fine roots were contained in the top 45cm of soil (except soil barrier) and in 75 to 105cm soil depth the fine roots were very less. The coarse root biomass under 0-60 cm soil depth contained 55 to 78% of its total biomass. The coarse root >20mm size contribute 92 to 97% of total coarse root biomass and 2-5,5-10 and 10-20 mm size coarse roots had 0.24 t01.98, 0.16 to 1.47 and 1.70 to 4.42% share respectively in total coarse root biomass. In tree-crop system, naturally growing trees had greater root biomass followed by pruning of trees up to 70% plant height. Root biomass in pure tree was less than agrisilviculture system. Tree-crop system had lower root: shoot biomass compared to pure tree and root-shoot biomass was lowest with pruning than trees allowed to grow normally.